Is self-perceived oral health status related to non-carious cervical lesions in Brazilian working adults? - Bomfim, Rafael Aiello; Crosato, Edgard (ARCHIVES OF HEALTH INVESTIGATION, 2018)
This study evaluates the association of Non Carious Cervical Lesions (NCCLs), Oral Health-Related Quality of Life (OHRQoL) and Work Ability Index (WAI) in a Brazilian population of Workers. One hundred workers were evaluated in a CEREST (Worker´s Health Reference Center). Participants were examined for oral disease following WHO recommendations, and the Oral Health Impact Profile (OHIP) and Work Ability Index assessment was used to determine OHRQoL and capacity to work, respectively. Assessment of tobacco use and alcohol consumption was made by Fagestron tolerance and Audit test. Statistical analyses were performed using STATA version 13.0. Dimensions with highest OHIP scores were physical pain and psychological discomfort. In bivariate analyses, NCCLs was significant associated with OHIP-14 severity PR 3.8 (CI95%1.26-11.89) and with self-related of oral pain PR 2.16 (CI95% 1.06-4.40). In the multivariate logistic regression analyses, years of smoking habits OR 1.73 (CI95% 1.03-2.9) was significant associated with OHIP-14 severity, independent of other variables. OHIP14 was significant associated to WAI (p=0,02). Strategies for Monitoring oral health Brazilian workers and reduce tobacco use should be done by Brazilian Companies to support Work ability. For future investigations on OHRQoL, analyses of NCCLs should be included. Descriptors: Quality of Life; Oral Health; Occupational Dentistry; Occupational Health; Tooth Erosion.